1987
DOI: 10.1029/rs022i003p00395
|View full text |Cite
|
Sign up to set email alerts
|

Data and theory for a new model of the horizontal structure of rain cells for propagation applications

Abstract: A large population of radar-measured ground rain cells is used to devise and assess a rain cell model for use in some of the future telecommunication applications. The model is based on cells of exponential profile (which is shown to reproduce best the point rain rate CDF); both rotational and biaxial symmetries are considered for the horizontal cross sections. Furthermore, the proposed model contains analytical expressions for the joint probability densities of the parameters which define the cell, i.e., peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
141
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 12 publications
1
141
1
4
Order By: Relevance
“…[59] The methodology developed by Goldhirsh [2000] to generate two-dimensional rain rate fields lies on the description of the rain rate horizontal distribution within the cells by the EXCELL model [Capsoni et al, 1987b]. Considering its monoaxial formulation, the analytical expression of the rain rate distribution within a cell is then given by:…”
Section: Methodology Of Goldhirshmentioning
confidence: 99%
See 4 more Smart Citations
“…[59] The methodology developed by Goldhirsh [2000] to generate two-dimensional rain rate fields lies on the description of the rain rate horizontal distribution within the cells by the EXCELL model [Capsoni et al, 1987b]. Considering its monoaxial formulation, the analytical expression of the rain rate distribution within a cell is then given by:…”
Section: Methodology Of Goldhirshmentioning
confidence: 99%
“…Considering a database of 213 112 rain cells identified at t = R 2 = 1 mm h À1 from the radar of Météo-France at Bordeaux in 1996 (southwestern France, midlatitude oceanic climate), and another database composed of 701 882 cells observed at the same threshold from the radar of Karlsruhe in 1999 (southwestern Germany, midlatitude continental climate), Féral et al [2003] have shown that, whatever the climatology, the HYCELL model enables one to improve the description of the rain rate horizontal distribution within the cells with respect to the well-known EXCELL model [Capsoni et al, 1987b].…”
Section: Hybrid Modeling Of the Rain Cell Horizontalmentioning
confidence: 99%
See 3 more Smart Citations